A comparative assessment of coronary artery calcification on chest CT scans of patients referred to a cardio-oncology clinic. Issue 1 (December 2016) - Brann, Alison; Bai, Charlotte; Hibbeln, John; Williams, Kim; Okwuosa, Tochi
Abstract Background The presence and burden of coronary artery calcium (CAC) is a strong predictor of cardiovascular events. In an effort to gain insight into the utility of CAC for coronary artery disease (CAD) screening in cancer patients with heart disease, we sought to determine the presence and burden of CAC detected on routine chest CT in patients referred to a cardio-oncology clinic, comparing them to a conventional cardiology clinic with the general population as controls. Methods Patients from the cardio-oncology clinic, general cardiology clinic, and the general clinic population at Rush University Medical Center who had a chest CT as part of their previous treatment were identified. Each CT scan was evaluated for presence, extent, and severity of CAC by 3 independent readers. Results In multivariate analysis, when compared with cardio-oncology clinic, CAC was more prevalent in the CT scans of cardiology patients (p  = 0.04), but not the general clinic population (p  = 0.5); CAC extent (p  = 0.05) and severity (p  = 0.05) was significantly higher in the cardiology patients but the extent (p  = 0.05) and severity (p  = 0.92) was similar in the general clinic population. Conclusion Despite being matched by age and sex, controlling for other major cardiovascular risk factors, patients referred to our cardio-oncology clinic had similar and less prevalent/severe CAC burden compared with the general population and conventional cardiology clinics respectively. Whether this translates to less utility of CAC for CAD screening, or to less overall coronary events in a cardio-oncology clinic, is of interest.